Neobacillus camarae sp. nov. a new bacterium isolated from the breast milk of a Senegalese mother breast-feeding a healthy child and genomic description of Neobacillus dielmonensis DSM 27844 FF4T and Neobacillus drentensis LMG 21831T - Salematou Sarr; Ousmane Ndour; Adama Mbow; Mamadou Beye; Anissa Idrissa Abdoulaye; Sara Bellali; Stephane Alibar; Rayan Semmar; Nicolas Orain; George Diatta; Camille Valles; Clemence Thiakane; et al. (Antonie van Leeuwenhoek, 2026)

Impact of climate change on the habitat range and distribution of Cordyla pinnata, Faidherbia albida and Balanites aegyptiaca in Senegal - Mariama Sambou; Brahima Koné; Seyni Sane; Mahunan Eric José Vodounnon; Andre Amakobo Diatta; Lamine Diatta; Bienvenu Sambou; Fatimata Diop; Simon Sambou; Malainy Diatta; Hyacinth Sambou; Assane Goudiaby; et al. (Modeling Earth Systems and Environment, 2024)

Advancements in earth observation for water resources monitoring and management in Africa: A comprehensive review - Timothy Dube; Dylan Seaton; Cletah Shoko; Cheikh Mbow (Journal of Hydrology, 2023)

Farmer Livelihood Strategies and Attitudes in Response to Climate Change in Agroforestry Systems in Kedougou, Senegal - Chad Papa; Pascal Nzokou; Cheikh Mbow (Environmental Management, 2020)

Urban tinkering - Thomas Elmqvist; José Siri; Erik Andersson; Pippin Anderson; Xuemei Bai; Pranab Kishore Das; Tatu Gatere; Andrew Gonzalez; Julie Goodness; Steven N. Handel; Ellika Hermansson Török; Jessica Kavonic; et al. (Sustainability Science, 2018)

Ground‐ and satellite‐based evidence of the biophysical mechanisms behind the greening Sahel - Martin Brandt; Cheikh Mbow; Abdoul A. Diouf; Aleixandre Verger; Cyrus Samimi; Rasmus Fensholt (Global Change Biology, 2015)
After a dry period with prolonged droughts in the 1970s and 1980s, recent scientific outcome suggests that the decades of abnormally dry conditions in the Sahel have been reversed by positive anomalies in rainfall. Various remote sensing studies observed a positive trend in vegetation greenness over the last decades which is known as the re‐greening of the Sahel. However, little investment has been made in including long‐term ground‐based data collections to evaluate and better understand the biophysical mechanisms behind these findings. Thus, deductions on a possible increment in biomass remain speculative. Our aim is to bridge these gaps and give specifics on the biophysical background factors of the re‐greening Sahel. Therefore, a trend analysis was applied on long time series (1987–2013) of satellite‐based vegetation and rainfall data, as well as on ground‐observations of leaf biomass of woody species, herb biomass, and woody species abundance in different ecosystems located in the Sahel zone of Senegal. We found that the positive trend observed in satellite vegetation time series (+36%) is caused by an increment of in situ measured biomass (+34%), which is highly controlled by precipitation (+40%). Whereas herb biomass shows large inter‐annual fluctuations rather than a clear trend, leaf biomass of woody species has doubled within 27 years (+103%). This increase in woody biomass did not reflect on biodiversity with 11 of 16 woody species declining in abundance over the period. We conclude that the observed greening in the Senegalese Sahel is primarily related to an increasing tree cover that caused satellite‐driven vegetation indices to increase with rainfall reversal.

Ecosystem properties of semiarid savanna grassland in West Africa and its relationship with environmental variability - Torbern Tagesson; Rasmus Fensholt; Idrissa Guiro; Mads Olander Rasmussen; Silvia Huber; Cheikh Mbow; Monica Garcia; Stéphanie Horion; Inge Sandholt; Bo Holm‐Rasmussen; Frank M. Göttsche; Marc‐Etienne Ridler; et al. (Global Change Biology, 2015)
The Dahra field site in Senegal, West Africa, was established in 2002 to monitor ecosystem properties of semiarid savanna grassland and their responses to climatic and environmental change. This article describes the environment and the ecosystem properties of the site using a unique set of in situ data. The studied variables include hydroclimatic variables, species composition, albedo, normalized difference vegetation index ( NDVI ), hyperspectral characteristics (350–1800 nm), surface reflectance anisotropy, brightness temperature, fraction of absorbed photosynthetic active radiation ( FAPAR ), biomass, vegetation water content, and land‐atmosphere exchanges of carbon ( NEE ) and energy. The Dahra field site experiences a typical Sahelian climate and is covered by coexisting trees (~3% canopy cover) and grass species, characterizing large parts of the Sahel. This makes the site suitable for investigating relationships between ecosystem properties and hydroclimatic variables for semiarid savanna ecosystems of the region. There were strong interannual, seasonal and diurnal dynamics in NEE , with high values of ~−7.5 g C m −2 day −1 during the peak of the growing season. We found neither browning nor greening NDVI trends from 2002 to 2012. Interannual variation in species composition was strongly related to rainfall distribution. NDVI and FAPAR were strongly related to species composition, especially for years dominated by the species Zornia glochidiata . This influence was not observed in interannual variation in biomass and vegetation productivity, thus challenging dryland productivity models based on remote sensing. Surface reflectance anisotropy (350–1800 nm) at the peak of the growing season varied strongly depending on wavelength and viewing angle thereby having implications for the design of remotely sensed spectral vegetation indices covering different wavelength regions. The presented time series of in situ data have great potential for dryland dynamics studies, global climate change related research and evaluation and parameterization of remote sensing products and dynamic vegetation models.

Co‐benefits, trade‐offs, barriers and policies for greenhouse gas mitigation in the agriculture, forestry and other land use ( AFOLU ) sector - Mercedes Bustamante; Carmenza Robledo‐Abad; Richard Harper; Cheikh Mbow; Nijavalli H. Ravindranat; Frank Sperling; Helmut Haberl; Alexandre de Siqueira Pinto; Pete Smith (Global Change Biology, 2014)
The agriculture, forestry and other land use ( AFOLU ) sector is responsible for approximately 25% of anthropogenic GHG emissions mainly from deforestation and agricultural emissions from livestock, soil and nutrient management. Mitigation from the sector is thus extremely important in meeting emission reduction targets. The sector offers a variety of cost‐competitive mitigation options with most analyses indicating a decline in emissions largely due to decreasing deforestation rates. Sustainability criteria are needed to guide development and implementation of AFOLU mitigation measures with particular focus on multifunctional systems that allow the delivery of multiple services from land. It is striking that almost all of the positive and negative impacts, opportunities and barriers are context specific, precluding generic statements about which AFOLU mitigation measures have the greatest promise at a global scale. This finding underlines the importance of considering each mitigation strategy on a case‐by‐case basis, systemic effects when implementing mitigation options on the national scale, and suggests that policies need to be flexible enough to allow such assessments. National and international agricultural and forest (climate) policies have the potential to alter the opportunity costs of specific land uses in ways that increase opportunities or barriers for attaining climate change mitigation goals. Policies governing practices in agriculture and in forest conservation and management need to account for both effective mitigation and adaptation and can help to orient practices in agriculture and in forestry towards global sharing of innovative technologies for the efficient use of land resources. Different policy instruments, especially economic incentives and regulatory approaches, are currently being applied however, for its successful implementation it is critical to understand how land‐use decisions are made and how new social, political and economic forces in the future will influence this process.

How much land‐based greenhouse gas mitigation can be achieved without compromising food security and environmental goals? - Pete Smith; Helmut Haberl; Alexander Popp; Karl‐heinz Erb; Christian Lauk; Richard Harper; Francesco N. Tubiello; Alexandre de Siqueira Pinto; Mostafa Jafari; Saran Sohi; Omar Masera; Hannes Böttcher; et al. (Global Change Biology, 2013)
Feeding 9–10 billion people by 2050 and preventing dangerous climate change are two of the greatest challenges facing humanity. Both challenges must be met while reducing the impact of land management on ecosystem services that deliver vital goods and services, and support human health and well‐being. Few studies to date have considered the interactions between these challenges. In this study we briefly outline the challenges, review the supply‐ and demand‐side climate mitigation potential available in the Agriculture, Forestry and Other Land Use AFOLU sector and options for delivering food security. We briefly outline some of the synergies and trade‐offs afforded by mitigation practices, before presenting an assessment of the mitigation potential possible in the AFOLU sector under possible future scenarios in which demand‐side measures codeliver to aid food security. We conclude that while supply‐side mitigation measures, such as changes in land management, might either enhance or negatively impact food security, demand‐side mitigation measures, such as reduced waste or demand for livestock products, should benefit both food security and greenhouse gas ( GHG ) mitigation. Demand‐side measures offer a greater potential (1.5–15.6 Gt CO 2 ‐eq. yr −1 ) in meeting both challenges than do supply‐side measures (1.5–4.3 Gt CO 2 ‐eq. yr −1 at carbon prices between 20 and 100 US$ t CO 2 ‐eq. yr −1 ), but given the enormity of challenges, all options need to be considered. Supply‐side measures should be implemented immediately, focussing on those that allow the production of more agricultural product per unit of input. For demand‐side measures, given the difficulties in their implementation and lag in their effectiveness, policy should be introduced quickly, and should aim to codeliver to other policy agenda, such as improving environmental quality or improving dietary health. These problems facing humanity in the 21st Century are extremely challenging, and policy that addresses multiple objectives is required now more than ever.

Planetary Stewardship in an Urbanizing World: Beyond City Limits - Sybil P. Seitzinger; Uno Svedin; Carole L. Crumley; Will Steffen; Saiful Arif Abdullah; Christine Alfsen; Wendy J. Broadgate; Frank Biermann; Ninad R. Bondre; John A. Dearing; Lisa Deutsch; Shobhakar Dhakal; et al. (Ambio, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Farmers’ Perceptions of Climate Change and Agricultural Adaptation Strategies in Rural Sahel - Ole Mertz; Cheikh Mbow; Anette Reenberg; Awa Diouf (Environmental Management, 2009)

A Local-Scale Study of the Trace Gas Emissions from Vegetation Burning around the Village of Dalun, Ghana, with Respect to Seasonal Vegetation Changes and Burning Practices - Christopher F. Saarnak; Thomas T. Nielsen; Cheikh Mbow (Climatic Change, 2003)